Circulating suPAR associates with severity and in‐hospital progression of COVID‐19. (4th May 2022) - Chalkias, Athanasios; Skoulakis, Anargyros; Papagiannakis, Nikolaos; Laou, Eleni; Tourlakopoulos, Konstantinos; Pagonis, Athanasios; Michou, Anastasia; Ntalarizou, Nicoletta; Mermiri, Maria; Ragias, Dimitrios; Bernal‐Morell, Enrique; Cebreiros López, Iria; et al.
Abstract: Background: COVID‐19 disease progression is characterized by hyperinflammation and risk stratification may aid in early aggressive treatment and advanced planning. The aim of this study was to assess whether suPAR and other markers measured at hospital admission can predict the severity of COVID‐19. Methods: The primary outcome measure in this international, multi‐centre, prospective, observational study with adult patients hospitalized primarily for COVID‐19 was the association of WHO Clinical Progression Scale (WHO‐CPS) with suPAR, ferritin, CRP, albumin, LDH, eGFR, age, procalcitonin, and interleukin‐6. Admission plasma suPAR levels were determined using the suPARnostic ® ELISA and suPARnostic ® Turbilatex assays. Results: Seven hundred and sixty‐seven patients, 440 (57.4%) males and 327 (42.6%) females, were included with a median age of 64 years. Log‐suPAR levels significantly correlated with WHO‐CPS score, with each doubling of suPAR increasing the score by one point ( p < .001). All the other markers were also correlated with WHO‐CPS score. Admission suPAR levels were significantly lower in survivors (7.10 vs. 9.63, 95% CI 1.47–3.59, p < .001). A linear model (SALGA) including suPAR, serum albumin, serum lactate dehydrogenase, eGFR, and age can best estimate the WHO‐CPS score and survival. Combining all five parameters in the SALGA model can improve the accuracy of discrimination with an AUC of 0.80 (95% CI: 0.759–0.836). Conclusions: suPAR levels significantly correlated with WHO‐CPS score, with each doubling of suPAR increasing the score by one point. The SALGA model may serve as a quick tool for predicting disease severity and survival at admission.